Influence of Perceived Benefit and Perceived Ease of Use on Purchase Decisions Using Electronic Payments with Price Discounts as Moderating - Lukiyana Lukiyana; Fani Sofiyanti (Budapest International Research and Critics University, 2022)
The background of this research is because of the rise of consumer purchasing decisions using e-payments in North Jakarta. The purpose of this research is to find out the influence of Perceived Benefit and Perceived Ease of Use on Purchase Decisions Using Electronic Payments with Price Discounts as Moderating. Perceived Benefit and Perceived Ease of Use are independent variables and Purchase Decision Using Electronic Payments is the dependent variable and there is a moderating variable, namely Price Discount. Data analysis method using SmartPLS. The population in this research are consumers who make purchases using e-payments in North Jakarta with a total sample of 160 respondents with purpose. The results of the study show that Perceived Benefits, Perceived Ease of Use, and Price Discounts have a positive and significant effect on Purchase Decisions Using Electronic Payments. Moderation Price Discount on Perceived Decisions Using Electronic Payments has a positive and significant effect, while moderating Price Discount on Perceived Ease of Use on Purchase Decisions Using Electronic Payments has a negative and significant effect.